Associations Between Perfusion Defects, Tissue Changes and Myocardial Deformation in Hypertrophic Cardiomyopathy, Uncovered by a Cardiac Magnetic Resonance Segmental Analysis - Brás, P (2022)
Background: Microvascular dysfunction is an often overlooked feature of hypertrophic cardiomyopathy (HCM). Our aim was to assess the association between microvascular dysfunction, wall thickness, tissue characteristics and myocardial deformation in HCM patients, by analyzing individual myocardial segments. Methods: Prospective assessment including cardiac magnetic resonance to assess wall thickness, T1 and T2 mapping, extracellular volume, late gadolinium enhancement (LGE) and stress perfusion. Results were stratified according to the 16 American Heart Association segments. Results: Seventy-five patients were recruited (1200 segments), 63% male, mean age 54.6±14.8 years, maximal wall thickness of 20.22±4.6 mm. Among the 424 segments (35%) with perfusion defects, 24% had defects only in the endocardial layer and 12% in both endocardial and epicardial layers. Perfusion defects were more often detected in hypertrophied segments (64%). Among the 660 segments with normal wall thickness, 19% presented perfusion defects. Independently of wall thickness, segments with perfusion defects had a higher T1 (β-estimate 30.28, p<0.001), extracelluar volume (β-estimate 1.50, p<0.001) and T2 (β-estimate 0.73, p<0.001) and had late gadolinium enhancement more frequently (odds ratio 4.16, p<0.001). Higher values of circumferential strain (lower deformation) and lower values of radial strain were found in segments with perfusion defects (β-estimate 2.76, p<0.001; and β-estimate -10.39, p<0.001, circumferential and radial strain, respectively). Conclusion: While microvascular dysfunction was more prevalent in more hypertrophied segments, it also had a major presence in segments without hypertrophy. In this segmental analysis, we found an association between the presence of ischemia and tissue abnormalities, replacement fibrosis as well as impaired strain, independently of the segmental wall thickness.